The discovery of the Americas: From prehistory through the age of Columbus - Maestro, Betsy; Maestro, Giulo (New York : Harper Collins Publisher, 1991)
Discusses both hypothetical and historical voyages of discovery to America by the Phoenicians, Saint Brendan of Ireland, the Vikings, and such later European navigators as Columbus, Cabot, and Magellan.
Keywords: Christopher Columbus -- American history -- Discovery of America